2017
DOI: 10.18632/oncotarget.23681
|View full text |Cite
|
Sign up to set email alerts
|

[Neratinib + Valproate] exposure permanently reduces ERBB1 and RAS expression in 4T1 mammary tumors and enhances M1 macrophage infiltration

Abstract: The irreversible ERBB1/2/4 inhibitor neratinib has been shown in vitro to rapidly reduce the expression of ERBB1/2/4 and RAS proteins via autophagic/lysosomal degradation. We have recently demonstrated that neratinib and valproate interact to suppress the growth of 4T1 mammary tumors but had not defined whether the [neratinib + valproate] drug combination, in a mouse, had altered the biology of the 4T1 cells. Exposure of 4T1 mammary tumors to [neratinib + valproate] for three days resulted, two weeks later, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 25 publications
(74 citation statements)
references
References 9 publications
2
71
0
Order By: Relevance
“…Trypsin-EDTA, DMEM, RPMI, penicillin-streptomycin were purchased from GIBCOBRL (GIBCOBRL Life Technologies, Grand Island, NY). Other reagents and performance of experimental procedures were as described (15,(20)(21)(22)(23)(24). Antibodies used: AIF (5318), BAX (5023), BAK (12105), BAD (9239), BIM (2933), BAK1 (12105), Beclin1 (3495), cathepsin B (31718), CD95 (8023), FADD (2782), eIF2α (5324), P-eIF2α S51 (3398), ULK-1 (8054), P-ULK-1 S757 (14202), P-AMPK S51 (2535), AMPKα (2532), P-ATM S1981 (13050), ATM (2873), ATG5 (12994), mTOR (2983), P-mTOR S2448 (5536), P-mTOR S2481 (2974), ATG13 (13468), MCL-1 (94296), BCL-XL (2764), P-AKT T308 (13038), P-ERK1/2 (5726), P-STAT3 Y705 (9145), P-p65 S536 (3033), p62 (23214), LAMP2 (49067) all from Cell Signaling Technology; P-ULK-1 S317 (3803a) from Abgent; P-ATG13 S318 (19127) from Novus Biologicals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trypsin-EDTA, DMEM, RPMI, penicillin-streptomycin were purchased from GIBCOBRL (GIBCOBRL Life Technologies, Grand Island, NY). Other reagents and performance of experimental procedures were as described (15,(20)(21)(22)(23)(24). Antibodies used: AIF (5318), BAX (5023), BAK (12105), BAD (9239), BIM (2933), BAK1 (12105), Beclin1 (3495), cathepsin B (31718), CD95 (8023), FADD (2782), eIF2α (5324), P-eIF2α S51 (3398), ULK-1 (8054), P-ULK-1 S757 (14202), P-AMPK S51 (2535), AMPKα (2532), P-ATM S1981 (13050), ATM (2873), ATG5 (12994), mTOR (2983), P-mTOR S2448 (5536), P-mTOR S2481 (2974), ATG13 (13468), MCL-1 (94296), BCL-XL (2764), P-AKT T308 (13038), P-ERK1/2 (5726), P-STAT3 Y705 (9145), P-p65 S536 (3033), p62 (23214), LAMP2 (49067) all from Cell Signaling Technology; P-ULK-1 S317 (3803a) from Abgent; P-ATG13 S318 (19127) from Novus Biologicals.…”
Section: Methodsmentioning
confidence: 99%
“…Freshly isolated GBM cells and activated microglia directly from the operating room were separated and grown in RPMI supplemented with 2.0% (v/v) fetal calf serum and 10% (v/v) Non-essential amino acids for 6 h, followed by drug exposure and viability assessments made the following day (15,(25)(26)(27). Cells were transfected with siRNA molecules or plasmids as described in prior manuscripts (20)(21)(22)(23)(24). Cells were transfected with a plasmid to express GFP-K-RAS V12 (0.1 µg) using lipofectamine 2000.…”
Section: Culture Transfection and In Vitro Exposure Of Cells To Drugsmentioning
confidence: 99%
“…Recent studies from our group have demonstrated that the irreversible ERBB1/2/4 inhibitor neratinib can increase autophagosome and autolysosome levels which are responsible for both the down-regulation of RTKs and RAS proteins, as well as causing tumor cell killing. [3][4][5] Thus, we next determined whether the autophagosome-inducing drug palbociclib interacted with the autophagosome-inducing drug neratinib to kill tumor cells. In mammary, colon, NSCLC, sarcoma, pancreatic and renal cancer cells neratinib and palbociclib interacted in an additive to greater than additive fashion to cause tumor cell death after 24h (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…In tumors, this alteration of biology can be observed up to two weeks after cessation of drug treatments. 5 For example, neratinib and valproate, through down-regulation of HDAC function and expression, alters the protein expression of immunogenic biomarkers. In the present studies we discovered that [neratinib + palbociclib] also could rapidly decrease the expression of PD-L1, PD-L2, IDO-1 and increase the levels of MHCA ( Figure S5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation